David Lynch swerves : uncertainty from Lost highway to Inland empire - Nochimson, Martha (UPCC book collections on Project MUSE. Film, Theater and Performing Arts., 2013)
The author draws on insights into the filmmaker’s creative sources to forge a template for analyzing Lynch’s recent films